Spectral solar radiation over and under sea ice during the MOSAiC expedition 2019/20, version 2.0 - Philipp Anhaus; Stefanie Arndt; Christian Katlein; Daniela Krampe; Benjamin Allen Lange; Ilkka Matero; Julia Regnery; Jan Rohde; Martin Schiller; Marcel Nicolaus (PANGAEA, 2025)
Solar radiation over and under drifting sea ice was measured using RAMSES hyper-spectral radiometers (TriOS) mounted on the remotely operated vehicle (ROV) during the Multidisciplinary drifting Observatory for the Study of Arctic Climate (MOSAiC) between November 2019 and September 2020. All data are given in full spectral resolution interpolated to 1.0 nm, integrated over the entire wavelength range (broadband, total: 320 to 950 nm), and integrated over the photosynthetically active radiation wavelength range (PAR: 400 to 700 nm). Two sensors were mounted on the ROV, an irradiance sensor (transmitted solar irradiance, ACC: Advanced-Cosine-Collector) for energy budget calculations and a radiance sensor (transmitted solar radiance, ARC: Advanced-Radiance-Collector with a 7° opening angle) to obtain high-resolution spatial variability. One additional radiometer was installed on the sea ice for surface reference measurements (incident solar irradiance, ACC). This is a raw data set, including all recorded spectra without any selection. Along with the radiation measurements, ROV positions were obtained from an acoustic Long Base Line (LBL) positioning system (LinkQuest Pinpoint). ROV depth was measured by a pressure sensor (Keller A-21Y, Keller AG). All times are given in Universal Coordinated Time (UTC).